فاعلية خدمات غرفة المصادر الإلكترونية في تحسين بعض المهارات الأكاديمية لدى عينة من التلاميذ ذوي صعوبات التعلم بمدارس مدينة تبوك - النجار، حسني زكريا السيد; البلوي، فيصل ناصر عيد (جامعة تبوك, 2018)
The aim of this research was to identify the effectiveness of the electronic resource room services in improving some of the academic skills in students with learning disabilities in the schools of Tabuk City. The sample consisted of (72) students of the learning disabilities program, divided into three groups: a first experimental group (24 students) who received the services of the electronic resource room, a second experimental group (24 students) who received the services of the regular resource room and a control group (24 students) did not receive the services of the resource room. The research tools included the services of the resource room in an electronic, the test of reading skills, the test of computations prepared by the researchers, The results were statistically analyzed using averages, standard deviation, T test, one-way ANOVA, Scheffe test, through SPSS, and indicated that there were statistically significant differences in reading skills and arithmetic between the pre-post measurements of the first experimental group who received the services of the electronic resource room and the second experimental group who received the services of the regular resource room in favor of the post-measurement. Also, a statistically significant differences has been indicated in reading skills and arithmetic among the three research groups: the first experimental , the second experimental and the control group in the post measurement in favor of the first experimental group and the second experimental group compared to the control group, which indicated the effectiveness of the electronic resource room services.
هدف البحث إلى الكشف عن فاعلية خدمات غرفة المصادر الإلكترونية في تحسين بعض المهارات الأكاديمية لدى التلاميذ ذوي صعوبات التعلم بمدارس مدينة تبوك، تكونت عينة البحث من (72) تلميذا من تلاميذ برنامج صعوبات التعلم تراوحت أعمارهم الزمنية بين 9.8- 11.4 سنة، جرى تقسيمهم إلى ثلاث مجموعات: مجموعة تجريبية أولى تكونت من (24) تلميذا تلقت خدمات غرفة المصادر الإلكترونية، ومجموعة تجريبية ثانية تكونت من (24) تلميذا تلقت خدمات غرفة المصادر العادية، ومجموعة ضابطة تكونت من (24) تلميذا لم تتلق خدمات غرفة المصادر، اشتملت أدوات البحث على خدمات غرفة المصادر بصورة إلكترونية، اختبار مهارات القراءة، اختبار العمليات الحسابية إعداد الباحثين، جرى تحليل نتائج البحث باستخدام المتوسطات والانحرافات المعيارية، اختبار)ت(، اختبار تحليل التباين الأحادي، اختبار شيفيه من خلال البرنامج الإحصائي SPSS، وأشارت نتائج البحث إلى وجود فروق دالة إحصائيا في مهارات القراءة والعمليات الحسابية بين القياسين القبلي والبعدي لتلاميذ المجموعة التجريبية الأولى التي تلقت خدمات غرفة المصادر الإلكترونية وتلاميذ المجموعة التجريبية الثانية التي تلقت خدمات غرفة المصادر العادية لصالح القياس البعدي، ووجود فروق دالة إحصائيا في مهارات القراءة والعمليات الحسابية بين المجموعات البحثية الثلاث: التجريبية الأولى والتجريبية الثانية والضابطة في القياس البعدي لصالح المجموعة التجريبية الأولى والمجموعة التجريبية الثانية مقارنة بالمجموعة الضابطة مما يشير إلى فاعلية خدمات غرفة المصادر الإلكترونية.
Keywords: التربية الخاصة -- الوسائل التعليمية -- المصادر الإلكترونية -- صعوبات التعلم -- المهارات الأكاديمية